Development and control of a 3-axis stabilised platform - Bredenkamp, Adolf Friedrich Ludwig (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.